2015
DOI: 10.1039/c5cp05172j
|View full text |Cite
|
Sign up to set email alerts
|

A new look at oxide formation at the copper/electrolyte interface by in situ spectroscopies

Abstract: The widely used engineering material copper is a prototype of an electrochemically passive metal. In this work, the passive films on evaporated copper in 0.1 M NaOH are investigated in situ and operando by spectroscopic ellipsometry and Raman spectroscopy, both conducted during oxidation in potentiostatic step experiments. Oxide growth is initiated by jumping from a potential at which the surface is oxide-free to -0.1 V vs. Ag|AgCl|3 M KCl (+0.11 V vs. standard hydrogen electrode, SHE). At subsequent electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 81 publications
1
44
1
Order By: Relevance
“…that for (a), so the noise due to adventitious water vapour at 1400 -1800 cm -1 is much more pronounced in (a). In the absence of CO2 and with application of -0.4 V (Fig 7 a), gains in absorbance 5 are seen at 1635, 1362, 1012 and 845 cm -1 corresponding to bands for bicarbonate, which are slightly shifted to higher wavenumber than reported for the solution anion 30 . This increase in bicarbonate concentration on application of -0.4 V suggests that the applied potential encourages surface adsorption of the anion.…”
Section: Stability Ofmentioning
confidence: 87%
See 1 more Smart Citation
“…that for (a), so the noise due to adventitious water vapour at 1400 -1800 cm -1 is much more pronounced in (a). In the absence of CO2 and with application of -0.4 V (Fig 7 a), gains in absorbance 5 are seen at 1635, 1362, 1012 and 845 cm -1 corresponding to bands for bicarbonate, which are slightly shifted to higher wavenumber than reported for the solution anion 30 . This increase in bicarbonate concentration on application of -0.4 V suggests that the applied potential encourages surface adsorption of the anion.…”
Section: Stability Ofmentioning
confidence: 87%
“…All of the readily available metals 3 , many metal alloys 4 , oxides 5 and sulphides 6 have been investigated as electrodes for CO2 reduction. The most promising and widely studied material is copper, as it the only metal to produce 30 hydrocarbons and appreciable quantities of >C1 products during CO2 reduction 7 . However, problems persist with poor faradaic efficiency (due to the competing H2 evolution reaction), poor product selectivity and loss of activity over time.…”
Section: Introductionmentioning
confidence: 99%
“…Copper ion release from the metal, and oxide film formation in biological test solution, are accepted to be the key for bacteria killing. 1,4,12,13 While a number of works are available addressing the surface film formation on copper in alkaline electrolytes, [14][15][16][17] much less physicalchemical data is available for conditions when active corrosion is possible, 18 and to our knowledge, the state of the surface during electrochemical polarization in a biochemical buffer has not been investigated. However, a number of reactions are possible in the typical biochemical buffers, in addition to those present in usual aqueous electrochemistry.…”
Section: -11mentioning
confidence: 99%
“…The film formation at the copper|electrolyte interface in general has been characterized by coupling electrochemical experiments to in situ characterization methods. [15][16][17] In situ Raman spectroscopy studies showed the potential dependent oxide formation. 18,35 Using their vibrational fingerprints in Raman spectroscopy, three main oxide phases of Cu can be easily identified.…”
Section: -11mentioning
confidence: 99%
See 1 more Smart Citation